Magneto‐Electrically Enhanced Intracellular Catalysis of FePt‐FeC Heterostructures for Chemodynamic Therapy. Issue 17 (23rd March 2021) - Zhang, Huilin; Li, Jinjin; Chen, Yang; Wu, Jiyue; Wang, Kun; Chen, Lijie; Wang, Ya; Jiang, Xingwu; Liu, Yanyan; Wu, Yelin; Jin, Dayong; Bu, Wenbo
Abstract: Intracellular catalytic reactions can tailor tumor cell plasticity toward high‐efficiency treatments, but the application is hindered by the low efficiency of intracellular catalysis. Here, a magneto‐electronic approach is developed for efficient intracellular catalysis by inducing eddy currents of FePt‐FeC heterostructures in mild alternating magnetic fields (frequency of f = 96 kHz and amplitude of B ≤ 70 mT). Finite element simulation shows a high density of induced charges gathering at the interface of FePt‐FeC heterostructure in the alternating magnetic field. As a result, the concentration of an essential coenzyme—β‐nicotinamide adenine dinucleotide—in cancer cells is significantly reduced by the enhanced catalytic hydrogenation reaction of FePt‐FeC heterostructures under alternating magnetic stimulation, leading to over 80% of senescent cancer cells—a vulnerable phenotype that facilitates further treatment. It is further demonstrated that senescent cancer cells can be efficiently killed by the chemodynamic therapy based on the enhanced Fenton‐like reaction. By promoting intracellular catalytic reactions in tumors, this approach may enable precise catalytic tumor treatment. Abstract : In a weak alternating magnetic field, the induced charges gathered at the interface of FePt‐FeC heterostructures are demonstrated to promote intracellular catalytic reduction of β‐nicotinamide adenine dinucleotide, leading to tumor cell senescence, thereby reducing resistance to treatments such as Fenton reaction‐based chemodynamic therapy. A one–two punch strategy is proposed and shows good therapeutic effects on tumors.